Soil-specific enzyme activity provides novel insight into the soil microbial necromass accumulation during sand dune fixation - Qu, Qing; Hai, Xuying (Frontiers in Microbiology, 2025)
IntroductionSoil enzymes are critical to plant growth and soil carbon turnover. However, the traditional method of assessing enzyme activity per unit of soil may be insufficient; instead, soil-specific enzyme activity per unit of soil organic carbon (SOCE) or microbial biomass carbon (MBCE) has been widely used to characterize soil carbon accumulation.MethodsWe systematically examined the changes in SOCE and MBCE with sand dune fixation (mobile, semi-mobile, semi-fixed, and fixed). We explored the implications of this soil-specific enzyme activity for soil microbial necromass carbon (NC) and soil organic carbon (SOC) accumulation.ResultsWe found that β-1, 4-glucosidase, β-D-cellobiosidase, β-1, 4-N-acetylglucosaminidase, and L-leucine aminopeptidase in SOCE and MBCE, the soil enzyme activity coefficient (SEAC), and the geometric mean of enzyme activity (GMEA) were significantly higher in semi-mobile, semi-fixed, and fixed dunes than those in mobile dunes. Furthermore, SOCE, MBCE, SEAC, and GMEA showed significant relationships with microbial NC and SOC. Specifically, soil-specific enzyme activity accounted for 32.2 and 24.1% of microbial NC and SOC variance, respectively.ConclusionDune fixation significantly increases SOCE and MBCE. More importantly, we recommend that changes in SOCE and MBCE should be widely used to assess microbial NC and SOC accumulation in degraded sandy land ecosystems.